REVIEW RECENT APPROACHES FOR THE SYNTHESIS OF HYBRID RESVERATROL MOLECULES AND THEIR BIOLOGICAL ACTIVITIES: A REVIEW - Amin Mohsin, Noor Ul; Irfan, Muhammad (Journal of the Chilean Chemical Society, 2018)
Resveratrol (RSV) is a polyphenol produced by different plant species having a variety of biological activities. Synthesis of hybrid molecules of RSV with different natural and synthetic compounds has been studied. These hybrid molecules have been prepared by using fused or merged techniques or by using some linker groups. Wittig method was mostly applied by using the appropriate ylides to prepare the RSV core. The hybrid molecules prepared by these techniques exhibited anticancer, anti-inflammatory, antioxidant, anti-alzheimer, metal chelating and enzyme inhibitory activities. These hybrid RSV molecules can serve as a lead compounds for the future design of new drug molecules.